Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.5435/jaaosglobal-d-22-00198
|View full text |Cite
|
Sign up to set email alerts
|

National Benchmarks for the Efficacy of Trigger Finger and the Risk Factors Associated With Failure

Abstract: Background: The purpose of this study was to compare the efficacy of single and multiple corticosteroid injections used for symptomatic trigger finger. The rates of subsequent injections and the rate of tendon sheath release are reported along with the identification of risk factors correlated with failure of injection. Methods: A retrospective review of a national healthcare database was conducted identifying patients with a diagnosis of trigger finger or thumb. Inclusion required a tendon sheath injection on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This therapy has been used in isolation, demonstrating an effectiveness in resolving symptoms of 60-70%, although it has also been used in combination with the use of orthoses or preoperatively, as in the study published by Kerrigan and Stanwix in 2009, in which it was concluded that the most successful and cost-effective management strategy for TF is the algorithm of two steroid injections before surgical intervention. 10,11 A systematic review published by Fleisch, et al in 2007, documented a 56% success rate with single steroid injection, while Lewis et al sought to document serial steroid injection, finding much more encouraging results, with symptom remission rates of 66.3%, 79.4% and 79.6% in the first, second and third injection, respectively. 12 Injection of steroids into the tendon sheath is a procedure that can be performed in an office, as long as the necessary aseptic conditions are available.…”
Section: Steroid Injectionmentioning
confidence: 99%
“…This therapy has been used in isolation, demonstrating an effectiveness in resolving symptoms of 60-70%, although it has also been used in combination with the use of orthoses or preoperatively, as in the study published by Kerrigan and Stanwix in 2009, in which it was concluded that the most successful and cost-effective management strategy for TF is the algorithm of two steroid injections before surgical intervention. 10,11 A systematic review published by Fleisch, et al in 2007, documented a 56% success rate with single steroid injection, while Lewis et al sought to document serial steroid injection, finding much more encouraging results, with symptom remission rates of 66.3%, 79.4% and 79.6% in the first, second and third injection, respectively. 12 Injection of steroids into the tendon sheath is a procedure that can be performed in an office, as long as the necessary aseptic conditions are available.…”
Section: Steroid Injectionmentioning
confidence: 99%